Di(2-ethylhexyl) phthalate-induced toxicity and peroxisome proliferator-activated receptor alpha: a review - Yuki Ito; Michihiro Kamijima; Tamie Nakajima (Komiyama Printing Co. Ltd, 2019)
Abstract The plasticizer di(2-ethylhexyl) phthalate (DEHP) has been widely used in the manufacture of polyvinyl chloride-containing products such as medical and consumer goods. Humans can easily be exposed to it because DEHP is ubiquitous in the environment. Recent research on the adverse effects of DEHP has focused on reproductive and developmental toxicity in rodents and/or humans. DEHP is a representative of the peroxisome proliferators. Therefore, peroxisome proliferator-activated receptor alpha (PPARα)-dependent pathways are the expected mode of action of several kinds of DEHP-induced toxicities. In this review, we summarize DEHP kinetics and its mechanisms of carcinogenicity and reproductive and developmental toxicity in relation to PPARα. Additionally, we give an overview of the impacts of science policy on exposure sources.